Fostering Higher-Level Inquiry in Online Asynchronous Discussion with Kit-Build Concept Mapping: A Case in Learning Linear Algebra - Hasani, Lintang Matahari; Junus, Kasiyah; Sadita, Lia; Hirashima, Tsukasa; Hayashi, Yusuke (Online Learning, 2025)
Online collaborative learning (OCL) based on the community of inquiry (CoI) framework is often implemented in the form of an online discussion activity for teaching subjects that require learners to revise understandings and invent ways to solve problems. However, implementing effective OCL for such a purpose is challenging due to the difficulty of fostering higher-level inquiry stages, which indicate deeper learning. Such an issue could hinder the effectiveness of the discussion and might lead to fewer transaction of ideas. Prior studies on OCL showed that facilitation strategies are insufficient for fostering higher-level inquiry stages. There is a need for an alternative strategy that could complement the existing approaches. Providing a preparatory activity that increases engagement with learning contents related to the discussion topic through a kit-build concept mapping (KBCM) activity could enable the participants to engage in a productive discussion by increasing their awareness of discussion-related concepts and their relationship. Such an activity may help the participants progress through the inquiry stages. This study aims to propose a preparatory activity for organizing knowledge using KBCM to support learners in advancing through practical inquiry stages during the discussion. The results show that participants who did KBCM showed a higher rate of triggering event, exploration, and integration compared to those who did summary writing. Therefore, providing KBCM as a preparatory activity has the potential to help learners progress through inquiry stages in a more productive way up until integration compared to the traditional method of reviewing materials through writing a structured summary.